The Role of Organizational Agility and Customer Participation in Enhancing Company Performance during Digital Transformation - Panutur, Sonny Sintong; Soehadi, Agus W.; Widjojo, Handyanto; Chandera, Yane (Universitas Prasetiya Mulya, 2025)
This research examines the factors that drive digital transformation and investigates the roles of organizational agility and customer participation in the transformation as key drivers of enhancing company performance. Using a quantitative method, data was collected from companies that have implemented digital transformation through an online survey. This study employed a partial least squares (PLS) structural equation model (SEM) to examine the proposed model using Smart PLS. The results indicate that technological, human, and environmental factors significantly influence a company's digital transformation. Furthermore, this research contributes to theory by integrating organizational agility and customer participation within the framework of digital transformation and its impact on company performance, as measured through operational efficiency, innovation performance, and profit growth. The findings highlight the importance of organizational agility amplifies its positive effects on operational efficiency, innovation performance, and profit growth, while customer participation plays a pivotal role, particularly in enhancing innovation performance.